MODELING OF THE LITHOSPHERE IN THE WHITE SEA REGION USING DECOMPOSITION OF ANOMALOUS GRAVITATIONAL AND MAGNETIC FIELDS - B. Z. Belashev; L. I. Bakunovich; N. V. Sharov (Геодинамика и тектонофизика, 2023)
The research area includes the White Sea and adjacent land located in the junction zone of the eastern part of the Fennoscandian Shield and the Russian Plate. The purpose of the study is to construct a model of the lithospheric structure of the region using decomposition of anomalous gravitational and magnetic fields and inverse problem solving for components of gravity and magnetic fields, respectively. The decompositions of the fields were provided by the singular spectral method in the software package "R 4.3.1". The inverse problems were solved using the programs of the "Integro" complex. The components of the fields help to identify and analyze buried geological structures. The rift system of the White Sea is most clearly represented by the fourth component of the gravitational and magnetic fields. The positions of density and magnetic inhomogeneities of the Earth’s crust corresponding the components of the fields have been determined. The component model is compared with the seismic density and magnetic models of the lithosphere along the 3-AР geotraverse (Kem – White Sea Throat).